Resilience and Posttraumatic Stress Disorder Symptoms in National Guard Soldiers Deployed to Iraq: A Prospective Study of Latent Class Trajectories and Their Predictors. Issue 4 (1st August 2017) - Polusny, Melissa A.; Erbes, Christopher R.; Kramer, Mark D.; Thuras, Paul; DeGarmo, Dave; Koffel, Erin; Litz, Brett; Arbisi, Paul A.
Abstract : This study examined the prospective course of posttraumatic stress disorder (PTSD) symptoms in a cohort of National Guard soldiers ( N = 522) deployed to combat operations in Iraq. Participants were assessed 4 times: 1 month before deployment, 2–3 months after returning from deployment, 1 year later, and 2 years postdeployment. Growth mixture modeling revealed 3 distinct trajectories: low‐stable symptoms, resilient, 76.4%; new‐onset symptoms, 14.2%; and chronic distress, 9.4%. Relative to the resilient class, membership in both the new‐onset symptoms and chronic distress trajectory classes was predicted by negative emotionality/neuroticism, odds ratios ( OR s) = 1.09, 95% CI [1.02, 1.17], and OR = 1.22, 95% CI [1.09, 1.35], respectively; and combat exposure, OR = 1.07, 95% CI [1.02, 1.12], and OR = 1.12, 95% CI [1.02, 1.24], respectively. Membership in the new‐onset trajectory class was predicted by predeployment military preparedness, OR = 0.95, 95% CI [0.91, 0.98], perceived threat during deployment, OR = 1.07, 95% CI [1.03, 1.10], and stressful life events following deployment, OR = 1.44, 95% CI [1.05, 1.96]. Prior deployment to Iraq or Afghanistan, OR = 3.85, 95% CI [1.72, 8.69], predeployment depression, OR = 1.27, 95% CI [1.20, 1.36], and predeployment concerns about a deployment's impact on civilian/family life, OR = 1.09, 95% CI [1.02, 1.16], distinguished the chronic distress group relative to the resilient group. Identifying predeployment vulnerability and postdeployment contextual factors provides insight for future efforts to bolster resilience, prevent, and treat posttraumatic symptoms.